Letter - Newport Industrial Committee, TUC Report, 11 May 1926 (page 2)
1926-05-11 "Letter - Newport Industrial Committee, TUC Report, 11 May 1926 (page 2)" [g0161002.jpg], 11 May 1926, Newport Industrial Committee